Content of leisure activity guidance recognized as necessary in special needs education - Kazuaki Maebara; Asuka Yamaguchi; Yukiya Yamada (Frontiers in Education)
This study aims to clarify the content of leisure activity guidance recognized by special needs education teachers and identify gaps in recognition of these between teachers and vocational rehabilitation practitioners who collaborate in transition support. This study surveyed a total of 255 participants, comprising 129 special needs school teachers and 126 vocational rehabilitation practitioners. The participants responded to a survey on the importance of leisure activity guidance, which was developed through a literature review on leisure activity guidance in special needs education and interviews with special needs education teachers. Factor analysis identified four factors of leisure activity guidance: establishing a foundation for leisure implementation, expanding options for leisure activities, recognizing the value of leisure, and acquiring skills for leisure implementation. While special needs education teachers recognized the importance of leisure activity guidance, qualitative differences in perception were observed between them and the vocational rehabilitation practitioners. The study clarified the essential content of leisure activity guidance in special needs education. The findings are expected to contribute to the qualitative improvement of transition support from special needs education to broader society.